2021
DOI: 10.1152/japplphysiol.00081.2021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of portable noninvasive ventilation on thoracoabdominal volumes in recovery from intermittent exercise in patients with COPD

Abstract: Background: We previously showed that use of portable non-invasive ventilation (pNIV) during recovery periods within intermittent exercise improved breathlessness and exercise tolerance in COPD patients compared to pursed-lip breathing (PLB). However, in a minority of patients recovery from dynamic hyperinflation (DH) was better with PLB, based on inspiratory capacity. We further explored this using Optoelectronic Plethysmography to assess total and compartmental thoracoabdominal volumes. Methods: Fourteen COP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Tis beneft appears similar for patients with a mild (pH 7.30 to 7.35) and a more severe nature (pH < 7.30) [14]. NIV corrects the mechanism leading to hypercapnia by increasing the tidal volume and by decreasing the work of breathing while reducing CO 2 [15]. Many studies indicated that the early use of NIV in mild AECOPD patients with a partial pressure of carbon dioxide (PaCO 2 ) >45 mmHg and a pH > 7.25 can efectively alleviate respiratory muscle fatigue.…”
Section: Discussionmentioning
confidence: 93%
“…Tis beneft appears similar for patients with a mild (pH 7.30 to 7.35) and a more severe nature (pH < 7.30) [14]. NIV corrects the mechanism leading to hypercapnia by increasing the tidal volume and by decreasing the work of breathing while reducing CO 2 [15]. Many studies indicated that the early use of NIV in mild AECOPD patients with a partial pressure of carbon dioxide (PaCO 2 ) >45 mmHg and a pH > 7.25 can efectively alleviate respiratory muscle fatigue.…”
Section: Discussionmentioning
confidence: 93%